(3OjhGf GdCHdg GdHZOGOjs - (3eMeO Hf HNJjGQ Hf YHO Gddg GdCHdg GdHZOGOjs ((3eMeO Hf WGgQ GdSeGhj s)
(3ChdgG (B:s
(3bGd GdCOjH GdaGVd eMeO Hf HNJjGQ GdeYQha cja GdTaGA hef Lahfc OGFj jGWGYf GdfLdGA HGdfLdGA s
(3BNQgG (B:s
(3hbGd jeOM GdhRjQ YVO GdOjf(B: (3hGSYO HPG GdYjH hGLYd YOGc ajg ef GdVMGjG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B15 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs